Effects of Board Structure on Firm Performance: A Comparison between Australia and Sri Lanka - Pratheepkanth, P.; Samanthala, H.; Wright, C.S. (Proceedings of 4th Global Business and Finance Research Conference, 2015)
This study analyses the correlation between Board attributes and firm performance in a sample of 100 Australian and 100 Sri Lankan firms to analyse. The board attributes analysed are size; gender ratio; non-independent-to-total members; and experience. The level of economic development is considered as an overlaying potential confounding effect on the outcomes. The analysis and a visual inspection of the raw data suggest that: Australian Boards are much larger than Sri Lankan Boards; in both nations, Boards are male dominated; and while board structure provides predictive insight into firm performance, only a few individual attributes are significant. The most important finding of this research is that the larger Boards of Australia appear to have a significantly stronger influence on firm performance than the relatively smaller boards of Sri Lanka. Future research should extend the review of the effects of Board size on corporate performance.
Keywords: Board structure; Board size; Independent directors and performance